High-quality genome assembly and multi-omics analysis of pigment synthesis pathway in Auricularia cornea - Ma, Xiaoxu; Lu, Lixin; Yao, Fangjie; Fang, Ming; Wang, Peng; Meng, Jingjing; Shao, Kaisheng; Sun, Xu; Zhang, Youmin (Frontiers in Microbiology, 2023)
Owing to its great market potential for food and health care, white Auricularia cornea, a rare edible fungus, has received increased attention in recent years. This study presents a high-quality genome assembly of A. cornea and multi-omics analysis of its pigment synthesis pathway. Continuous Long Reads libraries, combined with Hi-C-assisted assembly were used to assemble of white A. cornea. Based on this data, we analyzed the transcriptome and metabolome of purple and white strains during the mycelium, primordium, and fruiting body stages. Finally, we obtained the genome of A.cornea assembled from 13 clusters. Comparative and evolutionary analysis suggests that A.cornea is more closely related to Auricularia subglabra than to Auricularia heimuer. The divergence of white/purple A.cornea occurred approximately 40,000 years ago, and there were numerous inversions and translocations between homologous regions of the two genomes. Purple strain synthesized pigment via the shikimate pathway. The pigment in the fruiting body of A. cornea was γ-glutaminyl-3,4-dihydroxy-benzoate. During pigment synthesis, α-D-glucose-1P, citrate, 2-Oxoglutarate, and glutamate were four important intermediate metabolites, whereas polyphenol oxidase and other 20 enzyme genes were the key enzymes. This study sheds light on the genetic blueprint and evolutionary history of the white A.cornea genome, revealing the mechanism of pigment synthesis in A.cornea. It has important theoretical and practical implications for understanding the evolution of basidiomycetes, molecular breeding of white A.cornea, and deciphering the genetic regulations of edible fungi. Additionally, it provides valuable insights for the study of phenotypic traits in other edible fungi.